Give the equation of the asymptotes for the hyperbola x^2/36-y^2/4=1.

giorgiana1976 | Student

We'll recall the equation of hyperbola:

x^2/a^2 - y^2/b^2 = 1

We'll recall the equation that gives the two asymptotes of hyperbola:

y = `+-` (b/a)*x

Comparing the given equation of hyperbola to the general equation, we'll identify a and b:

a = +6 or a = -6

b = +2 or b = -2

y = +(2/6)*x or y = -(2/6)*x

The equations of the two asymptotes of the given hyperbola are: y = x/3 and y = -x/3.

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question